SUKUK AND BONDS IN INDONESIA: AN OVERVIEW - Witro, Doli; Setiawan, Iwan (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2021)
From the early 1920s to the late 20th century, there were at least 25 financial crises globally. In 2018, the Global Islamic Finance Report reported that Indonesia has tremendous potential to develop Islamic finance. Some of the Islamic financial products that can be developed in Indonesia are bonds and sukuk. Bonds are a product of the capital market. In its development, bonds have undergone relatively rapid innovation, which provides room for issuing Islamic bonds known as sukuk. This paper discusses the difference between sukuk and bonds. This paper aims to look at the differences between sukuk and bonds and the opportunities for issuance, application, and development of sukuk in Indonesia. This research is qualitative research that is literature. As for obtaining comprehensive results, this study uses two approaches consisting of a socio-historical approach and content analysis. The analysis results show that sukuk are in principle the same as bonds, with the main differences, among others, in the use of the concept of return and profit-sharing as a substitute for interest. Â Keywords: Sukuk; Bond; Sharia Bonds; Capital market; Indonesia